Comparison of efficacy and safety of topical glyceryl trinitrate vs. oral nifedipine in idiopathic perniosis: results of a randomized clinical trial - Khalid, Tanzeela; Maan, Muhammad Arif; Shehzad, Khurram (Journal of Pakistan Association of Dermatologists, 2016)
Objective To compare the therapeutic efficacy and safety of topical vasodilator glyceryl trinitrate (GTN) 0.4% cream, with systemic nifedipine (10-40mg/day) in patients with idiopathic perniosis (IP). Methods Patients with IP (n=65) were randomized into group A receiving GTN 0.4% cream (n=31) or group B receiving oral nifedipine, 10-40mg/day (n=34). They were evaluated for improvement in signs and symptoms and any side effects, every 15 days for six weeks. Primary outcome was efficacy and secondary outcome was side effects. Results 53 patients completed the study protocol. Twenty-three out of 26 (88%) patients in group A whereas 21 out of 27 (77%) in group B had complete clearance of lesions in six weeks (p=0.52). Clearance of lesions was achieved earlier (10.9 ±6 days) in group B as compared to (16.6±11.5 days) group A (p=0.05). Conclusion GTN 0.4% cream is an effective and safe alternative to oral nifedipine in the treatment of IP. Oral nifedipine leads to clearance of lesions earlier than GTN cream.